Factors affecting academicians’ acceptance on e-learning application / Nur A’fini Mohd Muzi … [et al.] - Mohd Muzi, Nur A’fini; Mohd Nadzir, Nur Aisyah; Abdul Mutalib, Sufiyatul Farhain; Mohamed Zukri, Shamsunarnie; Mohd Fauzi, Noor Zafarina (Akademi Pengajian Bahasa, 2021)
Electronic learning or E-learning is a term used to describe the action of knowledge gained through a computer-networked environment. E-learning is an approach that integrates learning with the use of emerging technologies in the learning process such as the internet, intranet, email, satellite broadcasting, audio or videotape, or compact disk read-only memory (CD-ROM). The creation and introduction of E-learning have been a prerequisite for an academic institution in the last decade. This is because E-learning offers advantages to universities such as lack of reliance on time limits, willingness to ask questions without shyness, and exposure to resources or materials from everywhere and anywhere. Hence, the readiness of an educator is one of the important factors affecting the success of online learning. The objective of this study is to determine factors that affect academicians in implementing online learning as their teaching style with the aim of supporting the development of content transmission in teaching and learning. The study design for this study was a cross-sectional study. An online questionnaire was distributed through the academicians' email and WhatsApp platforms. A total of 168 academicians were selected by using Proportionate Stratified Random Sampling where the population is divided into nine strata according to their faculties/academies. The variables involved were Gender, Educational Level and Working Experience, Computer Anxiety, Computer Self-Efficacy, Technological Complexity, Perceived Convenience, Perceived Usefulness and Perceived Ease of Use. Pearson Correlation test and Multiple Linear Regression were used as data analyses. There is a relationship between factors (computer self-efficacy, technological complexity, perceived convenience, perceived usefulness and perceived ease of use) and academicians’ acceptance on E-learning. Factor such as perceived ease of use and perceived usefulness are significantly affecting the academicians’ acceptance on E-learning. When the academicians perceived that online learning is ease to use and very useful, their acceptance on E-learning may increase. The further study was recommended to be done since this study found that computer self efficacy, technological complexity and perceived convenience had relationship with academicians’ acceptance on E-learning but not significantly contribute on it.